SEMIOTICAL APPROACH TO THE ANALYSIS OF CONCEPTS OF ARTISTIC ACTIVITY AND CREATION IN THE FINE ART - O.Ch. Chyrva (Academy of Cognitive and Natural Sciences, 2022)
The concepts of artistic activity> and creation, which were certain by soviet science, are analyzed in the article. On the basis of semiotical approach and consideration of different conceptions of artistic creation an attempt to deepen improvement of concepts of artistic activity and creation and designate the ways of improvement of educational process in opening of creative potential of students is done.